The Daydream cabin - Brown, Carolyn, 1948- (Montlake, 2020)
"A headstrong woman discovers it's never too late for change in New York Times bestselling author Carolyn Brown's spirited novel about lost hope and second chances. Substitute counselor for wayward teens isn't how public-school teacher Jayden Bennett planned to spend her summer vacation. However reluctant, she's hiking up her jeans and heading for remote Piney Wood Academy in north Texas. Two months. Seven days a week. Few amenities. And three troubled girls daring Jayden to make a difference. She understands what she's up against. She has her own burdens to bear. Jayden's not in it alone. The devoted elderly couple who run Piney Wood trusts in Jayden's tough-love approach to get the job done. So does drill instructor Elijah Thomas, whose hardened boot-camp hide conceals a heart broken one too many times. Jayden is making it beat again. For both of them, falling in love is a risk. Because all summers must come to an end. But with each new sunrise on these rustic acres, Jayden."--